The Cytoprotective Effect of Hyperoside against Oxidative Stress Is Mediated by the Nrf2-ARE Signaling Pathway through GSK-3β Inactivation. - Hai-Yan Xing; Yong-Qing Cai; Xian-Feng Wang; Lin-Li Wang; Pan Li; Guan-Ying Wang; Jian-Hong Chen (PLoS ONE)
Glycogen synthase kinase-3β (GSK-3β) acts as a negative regulator of NF-E2 related factor 2 (Nrf2) by inducing Nrf2 degradation and nuclear export. Our previous study demonstrated that the flavonoid hyperoside elicits cytoprotection against oxidative stress by activating the Keap1-Nrf2-ARE signaling pathway, thus increasing the expression of antioxidant enzymes, such as heme oxygenase-1 (HO-1), superoxide dismutase (SOD) and catalase. However, the role of GSK-3β in hyperoside-mediated Nrf2 activation is unclear. Here, we demonstrate that in a normal human hepatocyte cell line, (L02), hyperoside is capable of inducing the phosphorylation of GSK-3β at Ser9 without affecting the protein levels of GSK-3β and its phosphorylation at Thr390. Lithium chloride (LiCl) and short interfering RNA (siRNA)-mediated inhibition of GSK-3β significantly enhanced the ability of hyperoside to protect L02 liver cells from H2O2-induced oxidative damage, leading to increased cell survival shown by the maintenance of cell membrane integrity and elevated levels of glutathione (GSH), one of the endogenous antioxidant biomarkers. Further study showed that LiCl and siRNA-mediated inhibition of GSK-3β increased hyperoside-induced HO-1 expression, and the effect was dependent upon enhanced Nrf2 nuclear translocation and gene expression. These activities were followed by ARE-mediated transcriptional activation in the presence of hyperoside, which was abolished by the transfection of the cells with Nrf2 siRNA. Furthermore, the siRNA-mediated inhibition of Keap1 also enhanced hyperoside-induced Nrf2 nuclear accumulation and HO-1 expression, which was relatively smaller than the effects obtained from GSK-3β siRNA administration. Moreover, Keap1 siRNA administration alone had no significant effect on the phosphorylation and protein expression of GSK-3β. Collectively, our data provide evidence that hyperoside attenuates H2O2 -induced L02 cell damage by activating the Nrf2-ARE signaling pathway through both an increase in GSK-3β inhibitory phosphorylation at Ser9 and an inhibition of Keap1 and that hyperoside-mediated GSK-3β inhibition exhibits more significant effects.